Effect of fenofibrate on uric acid level in patients with gout - Jung, Ju-Yang (Sci Rep, 2018)
Gout is a chronic disease associated with deposition of monosodium urate crystals and accompanied by diabetes, hypertension, and dyslipidemia. Hypertriglyceridemia is common among patients with gout, and fenofibrate is usually used to reduce triglyceride levels. The aim of this study is to determine the effect of uric acid reduction by fenofibrate in patients with gout administered uric acid lowering agents (viz., the xanthine oxidase inhibitors allopurinol and febuxostat). Data from 863 patients with gout were collected from electronic medical records comprising information on underlying diseases, laboratory findings, and drug histories. Among all the patients, 70 (8.11%) took fenofibrate with allopurinol or febuxostat. Male and young patients took fenofibrate more frequently, and hypertension was less frequent in patients administered xanthine oxidase inhibitors and fenofibrate than in those administered only xanthine oxidase inhibitors. After the treatment, serum uric acid levels more significantly decreased (−1.81 ± 2.41 vs. −2.40 ± 2.28 mg/dL, p = 0.043) in patients with fenofibrate cotreatment, than in those administered allopurinol or febuxostat alone. The effect of uric acid reduction was larger (b = −1.098, p < 0.001) in patients taking glucocorticoids than in those administered other treatments. There was no difference in the levels of creatinine, blood urea nitrogen, and aminotransferases between patients treated with and without fenofibrate. Fenofibrate additionally reduced uric acid levels without showing any change in the results of renal or liver function tests, suggesting that the addition of fenofibrate is a reasonable option for treating gout in patients having high triglyceride levels.